2012
DOI: 10.1111/j.1439-0531.2008.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superovulation with oFSH and Norgestomet/GnRH‐Controlled Release of the LH Surge on Hormone Concentrations, and Yield of Oocytes and Embryos at Specific Developmental Stages

Abstract: The objective of this study was to evaluate a new superovulation procedure with oFSH after temporary suppression of the endogenous LH surge by norgestomet followed by administration of GnRH, to collect bovine oocytes and embryos at specific developmental stages. Since 1999, our research group applies this superovulation procedure with controlled release of the endogenous LH surge. The objective of this study is to verify if this procedure is reliable for collection of oocytes and embryos at specific time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In mono-ovulatory species such as humans and cows, ovarian stimulation with gonadotropins is widely used to stimulate the growing cohort of follicles to reach the ovulatory phase and produce an increased number of fertilizable oocytes as opposed to only one. The multiple FSH injections followed by a coasting period and an LH injection have been reported to generate developmentally competent oocytes and good to high embryonic developmental rates (Blondin et al 2002, Chaubal et al 2007, Knijn et al 2011. Although some differences in gene expression compared with natural cycles are expected, it has been demonstrated that stimulation with FSH, compared with those performed with eCG, has a profile of 17b-estradiol similar to those observed in a natural cycle (Soumano et al 1996, Knijn et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In mono-ovulatory species such as humans and cows, ovarian stimulation with gonadotropins is widely used to stimulate the growing cohort of follicles to reach the ovulatory phase and produce an increased number of fertilizable oocytes as opposed to only one. The multiple FSH injections followed by a coasting period and an LH injection have been reported to generate developmentally competent oocytes and good to high embryonic developmental rates (Blondin et al 2002, Chaubal et al 2007, Knijn et al 2011. Although some differences in gene expression compared with natural cycles are expected, it has been demonstrated that stimulation with FSH, compared with those performed with eCG, has a profile of 17b-estradiol similar to those observed in a natural cycle (Soumano et al 1996, Knijn et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The multiple FSH injections followed by a coasting period and an LH injection have been reported to generate developmentally competent oocytes and good to high embryonic developmental rates (Blondin et al 2002, Chaubal et al 2007, Knijn et al 2011. Although some differences in gene expression compared with natural cycles are expected, it has been demonstrated that stimulation with FSH, compared with those performed with eCG, has a profile of 17b-estradiol similar to those observed in a natural cycle (Soumano et al 1996, Knijn et al 2011). However, little was previously known about the gene expression cascade that follows the LH surge and the molecular determinants involved in ovulation and the last stage of GC differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations